Synthesis, crystal structure and Hirshfeld surface analysis of tert-butyl 4-[4-(difluoromethoxy)phenyl]-2,7,7-trimethyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate - Ezgi Pehlivanlar; Sema Öztürk Yıldırım; Rahime Şimşek; Mehmet Akkurt; Ray J. Butcher; Ajaya Bhattarai (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The 1,4-dihydropyridine ring of the title compound, C24H29F2NO4, adopts a distorted boat conformation, while the cyclohexene ring is in an almost twist-boat conformation. In the crystal, N—H...O and C—H...O hydrogen bonds as well as C—H...π interactions connect molecules, forming layers parallel to the (100) plane. These layers are linked by van der Waals forces and C—H...F interactions, which consolidate the crystal structure. Hirshfeld surface analysis shows the major contributions to the crystal packing are from H...H (54.1%), F...H/H...F (16.9%), O...H/H...O (15.4%) and C...H/H...C (12.6%) contacts.